Complicaciones postquirúrgicas en pacientes histerectomizadas, en el servicio de GinecoObstetricia del Hospital General Isidro Ayora - Contento Chocho, Karla Dayanna (2023)
Hysterectomy consists of the removal of the uterus by abdominal, vaginal and laparoscopy. Despite being one of the most performed gynecological interventions, it can generate post-surgical complications which cause negative consequences in patients, affecting their quality of life, endangering their health. The present research had as objective to determine the post-surgical complications in hysterectomized patients in the Gynecology-Obstetrics service at “Isidro Ayora” General Hospital in the Loja city during the period August-October 2021. To develop a nursing care guide that allows reducing the development of post-surgical complications, this is a retrospective, descriptive, quantitative and transversal study, for data collection a registration form was used, applied in 22 medical histories, who met the inclusion criteria, which allowed determining that in terms of sociodemographic factors, 59% of hysterectomized patients are between the ages of 41-50 years, 68% have finished high school and 77% reside in the urban area. 55% underwent a total hysterectomy, in relation to the approach route, 91% used the abdominal surgical technique, while the most frequent post-surgical complications were 91% pain, 14% presented fever and blending. Finally, the nursing attention guide was developed considering the 14 needs of Virginia Henderson and the NANDA, NOC and NIC taxonomies, which was delivered to the Gynecology-Obstetrics service with the purpose that it can be considered as support to provide quality care and reduce the appearance of possible complications